2013
DOI: 10.4103/1658-354x.109814
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose paravertebral blockade versus epidural blockade for pain relief after open renal surgery: A prospective randomized study

Abstract: Background:Paravertebral block (PVB) has been an established technique for providing analgesia to the chest and abdomen. We conducted the current study to compare single-dose PVB versus single-dose epidural blockade (EP) for pain relief after renal surgery.Methods:Eighty patients scheduled for renal surgery were randomly assigned into two groups according to the analgesic technique, PVB group or EP group. General anesthesia was induced for all patients. Postoperative pain was assessed over 24 h using 10-cm vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…However, it was managed effectively with boluses of ephedrine, atropine, and changing the depth of anesthesia without any morbidity. Our study was also consistent with the study of Hazem et al ( 23 ) in hemodynamics. No intraoperative fentanyl required in the three study groups, indicating the adequacy of analgesia produced by TPVB, which was consistent with Moller et al ( 24 ) and Mohta et al ( 25 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, it was managed effectively with boluses of ephedrine, atropine, and changing the depth of anesthesia without any morbidity. Our study was also consistent with the study of Hazem et al ( 23 ) in hemodynamics. No intraoperative fentanyl required in the three study groups, indicating the adequacy of analgesia produced by TPVB, which was consistent with Moller et al ( 24 ) and Mohta et al ( 25 ).…”
Section: Discussionsupporting
confidence: 94%
“…Opiate receptors stimulation on the central nervous system neurons leads to suppression of intracellular adenylyl cyclase, an opening of potassium channels, and closing of the calcium channels. This results in hyperpolarization of the cell membrane potential and suppression of action potential spread of ascending pain pathways ( 23 ). No statistically significant differences were found among the three groups relating to demographic data and operative features.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies used PVB as a proper anesthetic tool for patients underwent lithotripsy ,microwave ablation of kidney tumors or percutaneous nephrolithotomy [4,5&6]. Others compare the analgesic efficacy of PVB versus epidural block in nephrectomy and intravenous patient controlled analgesia [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Baik and colleagues looked at a single shot thoracic paravertebral block with IV PCA versus IV PCA alone and found that pain scores and fentanyl consumption were significantly lower in the paravertebral group [11]. Moawad et al compared paravertebral block and general anesthesia with epidural and general anesthesia in patients undergoing open renal surgery and found that paravertebral blockade has similar analgesic outcomes but is associated with greater hemodynamic stability than epidural anesthesia [12].…”
Section: Clinical Evidencementioning
confidence: 99%
“…Epidurals require close management of perioperative anticoagulation and can be associated with hypotension, dural puncture, and high failure rates. Richardson et al compared thoracic paravertebral infusions with epidural infusions in patients undergoing thoracotomies [12]. The infusions were initiated prior to incision and were continued into the post-operative period and all patients received multimodal analgesia consisting of perioperative opioids and NSAIDS.…”
Section: Clinical Evidencementioning
confidence: 99%